2021
DOI: 10.3389/fphar.2021.719589
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Attenuates Silica-Induced Pulmonary Fibrosis by Activating Autophagy via the AMPK-mTOR Signaling Pathway

Abstract: Long-term exposure to crystalline silica particles leads to silicosis characterized by persistent inflammation and progressive fibrosis in the lung. So far, there is no specific treatment to cure the disease other than supportive care. In this study, we examined the effects of metformin, a prescribed drug for type || diabetes on silicosis and explored the possible mechanisms in an established rat silicosis model in vivo, and an in vitro co-cultured model containing human macrophages cells (THP-1) and human bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 101 publications
2
38
0
Order By: Relevance
“…The fibroblast-MΦ crosstalk underlying the therapeutic mechanism of metformin for arthrofibrosis is the novel finding of the present study. Previous similar studies largely focused on the cell-autonomous effect of metformin (Feng et al, 2017;Han et al, 2021;Kheirollahi et al, 2019;Li et al, 2021;McCloskey et al, 2020;Mummidi et al, 2016;Rangarajan et al, 2018;Sato et al, 2016;Tang et al, 2021), while the present study extended the mechanism of action of the drug by providing new evidence that metformin-induced fibroblast metabolic rewiring not only plays a cellautonomous role but also involves a noncell-autonomous role in the resolution of arthrofibrosis.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The fibroblast-MΦ crosstalk underlying the therapeutic mechanism of metformin for arthrofibrosis is the novel finding of the present study. Previous similar studies largely focused on the cell-autonomous effect of metformin (Feng et al, 2017;Han et al, 2021;Kheirollahi et al, 2019;Li et al, 2021;McCloskey et al, 2020;Mummidi et al, 2016;Rangarajan et al, 2018;Sato et al, 2016;Tang et al, 2021), while the present study extended the mechanism of action of the drug by providing new evidence that metformin-induced fibroblast metabolic rewiring not only plays a cellautonomous role but also involves a noncell-autonomous role in the resolution of arthrofibrosis.…”
Section: Discussionsupporting
confidence: 61%
“…Several reports have shown that metformin can prevent and even reverse fibrotic processes in multiple organs, including the kidney, lung, and liver (Feng et al, 2017; Han et al, 2021; Kheirollahi et al, 2019; Li et al, 2021; McCloskey et al, 2020; Mummidi et al, 2016; Rangarajan et al, 2018; Sato et al, 2016; Tang et al, 2021). A recent study confirmed the positive effect of metformin in suppressing joint capsular fibrosis in a mouse model of knee contracture (Tokuda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the PI3K/Akt pathway is involved in various biological processes, several on-target and off-target effects may be observed, which can limit the clinical development of AGING therapeutics. AMPK activators such as metformin, AICAR, poricoic acid A, and HL156A may function as potential therapeutic agents for both fibrosis and cancer in aging organs [61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was indicated that the administration of metformin blunted fibrosis in a rat model induced by silica via the regulation of the AMPK-mTOR axis and induction of P62, Beclin-1, and LC3. Histological examination revealed the phenotype acquisition of pneumocytes within the lung parenchyma ( Li et al, 2021 ). Regarding the close relationship between mTOR and autophagy response, the application of pharmacological agents with the potential to regulate mTOR activity is an appropriate strategy for the regulation of NP.…”
Section: Autophagy and Analgesiamentioning
confidence: 99%